Efektivitas pembelajaran daring di masa pandemi Covid-19 terhadap hasil belajar siswa SD - Wardaini, Dina Oktaviana (ARKA INSTITUTE, 2022)
The development of education today is influenced by the rapid progress of information and communication technology. One of the information technologies that play a role in the world of education is online learning. Online learning functions as a liaison between educators and students with an internet network that can be accessed anytime and anywhere. The online media used by the research subjects are various (WhatsApp, Google Classroom, Website). The purpose of this study was to analyze the effectiveness of online learning applied to the elementary school level. The method collected in data collection was a question and answer session with the sources, namely elementary school students via WhatsApp and the results of observations made by researchers during online learning. The research results show that online learning is effective and efficient if the material delivered by the teacher is optimal and carried out with parental assistance. It can be concluded that student learning outcomes have improved with online learning, although there are still several shortcomings.